Dopamine D1 receptor modulation in nucleus accumbens lowers voluntary wheel running in rats bred to run high distances - Roberts, Michael D.; Gilpin, Leigh; Parker, Kyle E.; Childs, Thomas E.; Will, Matthew J.; Booth, Frank W. (Physiology & behavior, 2012)
Dopamine signaling in the nucleus accumbens (NAc) has been postulated to influence reward development towards drugs of abuse and exercise. Herein, we used generation 4–5 rats that were selectively bred to voluntary run high (HVR) versus low (LVR) distances in order to examine if dopamine-like 1 (D1) receptor modulation in the NAc differentially affects nightly voluntary wheel running between these lines. A subset of generation 5–6 HVR and LVR rats were also used to study the mRNA expression of key genes related to reward and addiction in the NAc (i.e., DRD1, DRD5, DRD2, Nr4a2, FosB, and BDNF). In a crossover fashion, a D1-like agonist SKF 82958 (2μg per side) or D1-like full antagonist SCH 23390 (4μg per side) was bilaterally injected into the NAc of HVR and LVR female Wistar rats prior to their high running nights. Notably, during hours 2–4 (between 2000 and 2300) of the dark cycle there was a significant decrement in running distances in the HVR rats treated with the D1 agonist (p=0.025) and antagonist (p=0.017) whereas the running distances in LVR rats were not affected. Interestingly, HVR and LVR rats possessed similar NAc concentrations of the studied mRNAs. These data suggest that: a) animals predisposed to run high distances on a nightly basis may quickly develop a rewarding response to exercise due to an optimal D1-like receptor signaling pathway in the NAc that can be perturbed by either activation or blocking, b) D1-like agonist or antagonist injections do not increase running distances in rats that are bred to run low nightly distances, and c) running differences between HVR and LVR animals are seemingly not due to the expression of the studied mRNAs. Given the societal prevalence of obesity and extraneous physical inactivity, future studies should be performed in order to further determine the culprit for the low running phenotype observed in LVR animals. ► Rats were selectively bred to voluntarily to run high (HVR) or low (LVR) distances. ► Role of nucleus accumbens (NAc) in motivation to voluntarily run was tested. ► Dopamine D1 agonist and antagonist NAc injections lower the distance of HVR, but not LVR. ► NAc is necessary for motivation to voluntarily run long distances in rats. ► 5th generation HVR and LVR rats have same ‘reward’-related mRNAs in the NAc.